Effect of Wheels, Casters and Forks on Vibration Attenuation and Propulsion Cost of Manual Wheelchairs - Jacob P. Misch; Yuanning Liu; Stephen Sprigle (IEEE, 2022)
Manual wheelchair users are exposed to whole-body vibrations as a direct result of using their wheelchair. Wheels, tires, and caster forks have been developed to reduce or attenuate the vibration that transmits through the frame and reaches the user. Five of these components with energy-absorbing characteristics were compared to standard pneumatic drive wheels and casters. This study used a robotic wheelchair propulsion system to repeatedly drive an ultra-lightweight wheelchair over four common indoor and outdoor surfaces: linoleum tile, decorative brick, poured concrete sidewalk, and expanded aluminum grates. Data from the propulsion system and a seat-mounted accelerometer were used to evaluate the energetic efficiency and vibration exposure of each configuration. Equivalence test results identified meaningful differences in both propulsion cost and seat vibration. LoopWheels and SoftWheels both increased propulsion costs by 12-16% over the default configuration without reducing vibration at the seat. Frog Legs suspension caster forks increased vibration exposure by 16-97% across all four surfaces. Softroll casters reduced vibration by 11% over metal grates. Wide pneumatic ‘mountain’ tires showed no difference from the default configuration. All vibration measurements were within acceptable ranges compared to health guidance standards. Out of the component options, softroll casters show the most promising results for ease of efficiency and effectiveness at reducing vibrations through the wheelchair frame and seat cushion. These results suggest some components with built-in suspension systems are ineffective at reducing vibration exposure beyond standard components, and often introduce mechanical inefficiencies that the user would have to overcome with every propulsion stroke.